2007
DOI: 10.1093/nar/gkm153
|View full text |Cite
|
Sign up to set email alerts
|

HIV controls the selective packaging of genomic, spliced viral and cellular RNAs into virions through different mechanisms

Abstract: In addition to genomic RNA, HIV-1 particles package cellular and spliced viral RNAs. In order to determine the encapsidation mechanisms of these RNAs, we determined the packaging efficiencies and specificities of genomic RNA, singly and fully spliced HIV mRNAs and different host RNAs species: 7SL RNA, U6 snRNA and GAPDH mRNA using RT-QPCR. Except GAPDH mRNA, all RNAs are selectively encapsidated. Singly spliced RNAs, harboring the Rev-responsible element, and fully spliced viral RNAs, which do not contain this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
167
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(181 citation statements)
references
References 49 publications
14
167
0
Order By: Relevance
“…Consequently, the deletions of SL3 included flanking regions and, in our opinion, it is likely to be that many of the RNA mutants used in these studies adopted aberrant structures. More recent works using exact deletions of SL3 show more modest effects on packaging 6,31 , in agreement with our results. Furthermore, our data are totally consistent with the observation that deletions of SL1 have profound effect on gRNA packaging, while substitutions of the SL1 apical loop that affect gRNA dimerization have modest effects 30,33 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consequently, the deletions of SL3 included flanking regions and, in our opinion, it is likely to be that many of the RNA mutants used in these studies adopted aberrant structures. More recent works using exact deletions of SL3 show more modest effects on packaging 6,31 , in agreement with our results. Furthermore, our data are totally consistent with the observation that deletions of SL1 have profound effect on gRNA packaging, while substitutions of the SL1 apical loop that affect gRNA dimerization have modest effects 30,33 .…”
Section: Discussionsupporting
confidence: 93%
“…2). The 410-fold reduced binding of Pr55 Gag to spliced RNAs compares well with quantitative packaging studies showing that gRNA is incorporated 50-100-fold more efficiently than spliced RNAs into HIV-1 viral particles 6 . Thus, selection during the initial binding event appears to be the main factor governing selective packaging of the gRNA, even though other pathways such as the gRNA nuclear export pathway and subcellular localization might also play a significant role 7,8 .…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…It has been reported that the RNA has a crucial role in the structural integrity of the retroviral particle and that selective and non-selective packaging of cellular RNAs can occur both in murine leukemia virus and in HIV-1 particles. 41,44,45 Moreover, it has been shown that HIV-1-based vectors with deletions of SL1-SL4, the region encompassing sequences involved in targeting viral RNA into virions as high-affinity binding site for Gag, 46,47 can still be packaged and transduced, although with no apparent normal dimerization, suggesting the presence of a c-independent mechanism of packaging. 48 Thus, alternative and not mutually exclusive explanations have to be taken into account to explain the lack of high efficiency of pseudotyped HIV-1 particles transducing ability.…”
Section: Sfv/hiv Hybrid Vectors C Del Vecchio Et Almentioning
confidence: 99%